The Role Of Accounting In The Growth Of Msmes In Indonesia - Yuliati, Anik; Huda, Syamsul (Winter Journal: IMWI Student Research Journal, 2025)
Accounting is crucial to the growth of MSMEs in Indonesia, as it provides accurate financial information, facilitates planning, enhances credibility, and ensures tax compliance. However, many MSMEs still lack a basic understanding of accounting, which hinders their business development due to a lack of comprehension of financial records. This research aims to examine the role of accounting in Micro, Small, and Medium Enterprises (MSMEs) and the factors that influence their growth in Indonesia. This research employs a qualitative approach, utilizing a literature study method that draws on the latest scientific articles from the past decade and credible e-books to examine the role of accounting in MSMEs and the factors influencing their growth in Indonesia. The results indicate that accounting plays a crucial role in supporting the growth of MSMEs in Indonesia by providing accurate financial information and facilitating effective planning and resource management. Various internal factors, including the quality of human resources, financial aspects, technical operations, and marketing, also influence the growth of MSMEs. External factors include government policies, socioeconomic and cultural conditions, and the role of institutions. This study aims to provide recommendations for MSME actors and policymakers to enhance effective accounting practices for sustainable economic growth.